Revisiting the environmental Kuznets curve (EKC) hypothesis in India: the effects of energy consumption and democracy - Usman, Ojonugwa; Iorember, Paul Terhemba; Olanipekun, Ifedolapo O. (Springer Heidelberg, 2019)
The study revisits the position of the environmental Kuznets curve (EKC) hypothesis in India by incorporating the role of energy consumption and democratic regime in the environmental degradation function for the period 1971-2014. Employing Zivot-Andrews nonstationarity test, Bayer-Hanck cointegration test, autoregressive distributed lag (ARDL) model, and vector autoregressive model (VECM) Granger causality test, the results found the integration order of I(1) and a stable cointegration among the series. The result validates the EKC hypothesis for India and further divulges that while energy consumption increases environmental degradation both in the long run and short run; the effect of democracy in reducing environmental degradation is weak (statistically insignificant) in the long run but strong (statistically significant) in the short run. The finding from the VECM Granger causality test indicates a long-run causality between the fundamental variables and environmental degradation. Furthermore, the results of the short run show a unidirectional Granger causality running from energy consumption to environmental degradation, energy consumption to real income, and energy consumption to square of real income. Therefore, our findings suggest that energy conservation policy should be prioritized towards harnessing energy from clean sources to mitigate environmental degradation and spur economic growth.
Keywords: Energy consumption; Environmental degradation; Democracy; VECM Granger causality; India